Feasibility of coronary access in patients with acute coronary syndrome and previous TAVR - Kim, Won-Keun; Leuschner, Florian; Hamm, Christian; Sinning, Jan-Malte (JACC Cardiovascular interventions, 2021)
Objectives - The aim of this study was to characterize the feasibility of coronary angiography (CA) and percutaneous coronary intervention (PCI) in acute settings among patients who have undergone transcatheter aortic valve replacement (TAVR). - Background - Impaired coronary access after TAVR may be challenging and particularly in acute settings could have deleterious consequences. - Methods - In this international registry, data from patients with prior TAVR requiring urgent or emergent CA were retrospectively collected. A total of 449 patients from 25 sites with acute coronary syndromes (89.1%) and other acute cardiovascular situations (10.9%) were included. - Results - Success rates were high for CA of the right coronary artery (98.3%) and left coronary artery (99.3%) and were higher among patients with short stent-frame prostheses (SFPs) than in those with long SFPs for CA of the right coronary artery (99.6% vs 95.9%; P = 0.005) but not for CA of the left coronary artery (99.7% vs 98.7%; P = 0.24). PCI of native coronary arteries was successful in 91.4% of cases and independent of valve type (short SFP 90.4% vs long SFP 93.4%; P = 0.44). Guide engagement failed in 6 patients, of whom 3 underwent emergent coronary artery bypass grafting and another 3 died in the hospital. Among patients requiring revascularization of native vessels, independent predictors of 30-day all-cause mortality were prior diabetes, cardiogenic shock, and failed PCI but not valve type or success of coronary engagement. - Conclusions - CA or PCI after TAVR in acute settings is usually successful, but selective coronary engagement may be more challenging in the presence of long SFPs. Among patients requiring PCI, prior diabetes, cardiogenic shock, and failed PCI were predictors of early mortality.